PENGARUH MANAJEMEN LABA, RASIO KEUANGAN TERHADAP PERINGKAT OBLIGASI - Petty Arisanti; Eko Prasetyo; Rini Ratna Nafitasari (P3M Politeknik Negeri Banjarmasin, 2022)
Investments are classified into two types, namely investments in ownership certificates (shares) and investments in debt securities (bonds). The Indonesia Stock Exchange defines bonds as transferable medium-long term debt securities containing a promise from the issuing party to pay the imbalance in the form of interest in a certain period and principal at a predetermined time to the buyer of the bonds. The type of data used in this study is secondary data in the form of annual financial statements listed on the Indonesia Stock Exchange (IDX). The results of the study show that: (1) earnings management has an effect on bond ratings; (2) liquidity ratio has an effect on bond rating; and (3) the activity ratio has no effect on bond ratings.